Wood pole structures for electrical transmission lines : recommended practice for design and use - McGuire, James M., 1963-; Lynch, Otto J.; Schneider, Vicki (American Society of Civil Engineers, 2019)
Wood Pole Structures for Electrical Transmission Lines: Recommended Practice for Design and Use, MOP 141, provides comprehensive knowledge of the principles and methods for the design and use of wood poles for overhead utility line structures. The use of wood pole structures, properly designed utilizing consistent structural engineering principles, may provide a simple, cost effective, and more resilient option than some of the other pole materials commonly used.
Keywords: Electric lines -- United States -- Poles and towers -- Design and construction.; Electric lines -- Poles and towers -- Installation -- United States.; Wood poles.; elektronické knihy; electronic books